Analysis of the Influence of Work Environment, Human Resource Management, and Information Systems on PT.XYZ Performance with Operational Efficiency and Employee Productivity as Mediating Variables - Ekwan Setyo Utomo; Slamet Riyadi; Fausta Ari Barata (International Forum of Researchers and Lecturers, 2025)
In the era of globalization and rapid technological advances, the scope of operational management is increasingly expanding. In facing global competition, companies must be able to face challenges in their operational management. The purpose of this study is to determine the factors that influence organizational performance through operational efficiency and employee productivity. The population used is all employees at PT. XYZ with a total of 107 employees. The sampling technique used in this study is a saturated sample where all members are filled in as samples in the study as many as 107 employees. This study uses the SEM (structure Equation Modeling) method with the AMOS tool. The results of the study indicate that the Work Environment has a significant effect on operational efficiency. Employee productivity, and organizational performance. Human resource management has a significant effect on operational efficiency, employee productivity, and organizational performance. Information systems have a significant effect on operational efficiency, employee productivity, and organizational performance. Operational efficiency has a significant effect on organizational performance. And employee productivity has a significant effect on organizational performance.